Developing the Skills of Mentally Retarded Children Through Career Guidance - Ahmad Fadhi; Peni Ramanda; Sulihat (International Journal of Pedagogy, 2023)
One of the problems faced by mentally retarded children at SKH Negeri 01 Cilegon City is the difficulty in seeking further education guarantees for the development of their abilities or independence as career achievements and talents for themselves, even though every child has their potential. The method used is descriptive qualitative to present a detailed description of the social situation or clarify a phenomenon under study. Data was collected using observation techniques, interviews and documentation. This research was conducted in July-October 2022 with 3 respondents consisting of 3 children, namely IS, SZ, QA, and informants consisting of 3 people, namely class teachers, school principals, and parents of mentally retarded children. The conclusions of this study: 1) Planning for career guidance for mentally retarded children at SKH Cilegon City is in accordance with existing procedures and services. 2) The implementation of career guidance for mentally retarded children at SKH Cilegon City is carried out according to a predetermined time with several activities, namely music, singing, swimming, cooking, batik and others. 3) Evaluation at SKH Cilegon City, namely by looking at the child’s development, ability, and independence, and always paying attention to the results of all career guidance programs. 4) Supporting factors, namely: from educators, students and infrastructure.